Crew scheduling models in airline disruption management - Xindu Chen; Xin Chen; Xinhui Zhang (2010 IEEE 17Th International Conference on Industrial Engineering and Engineering Management, 2010)
This paper investigates the intra-fleet and inter-fleet model for the solution of crew scheduling problem during airline irregular operations. The intra-fleet model is widely adopted in the airline industry where flight is grouped together and works typically within a fleet. The inter-fleet model on the other hand, splits of flight attendant groups and reassign of them across different fleet. Though both these two models belong to the set covering problem with side constraints, the former is a 0-1 set covering problem while the latter is a general set covering problem, they exhibit different computational characteristics and a simulated annealing algorithm is developed and applied for models that are difficult to solve. Our results also show that the intra-fleet model, though widely used in practice, limits the solution space and could lead to inferior solutions; the inter-fleet model, on the other hand, offers much better solutions that could save millions of dollars for airlines.